THE DETERMINANT OF FACTORS THAT INFLUENCE THE DEMAND OF MORTGAGE LOAN (A Case Study in Bank Tabungan Negara (BTN) University of Brawijaya Branch office malang in 2008 – 2012) - Aulia Ratuningtyas; Farah Wulandari Pangestuty (Jurnal Ilmiah Mahasiswa FEB, 2013)
By using secondary data obtained from BTN University of Brawijaya Branch Office Malang  and Central Bureau of Statistics (BPS) Malang  in 2008 to 2012 and multiple regression analysis, this study  is aimed to analyze  the factors that influence the demand of mortgage loan in BTN University of Brawijaya Branch Office Malang from 2008 to 2012. BTN is the biggest bank in Indonesia that provides mortgage loan as the main product. The results of multiple regression analysis show that the factors include  lending rate, inflation,  income, and exchange rate  are simultaneously influence the demand of mortgage loan. Inflation and income have  significant influence  towards  the demand of mortgage loan, but lending rate and exchange rate has insignificant influence towards the demand of mortgage loan.Keywords:  The demand of  mortgage loan, lending rate, inflation,  income, exchange rate